The Bona Fide Body: Title VII’s Last Bastion of Intentional Sex Discrimination - McGowan, Sharon M. (Columbia Journal of Gender and Law, 2003)
Under a classic view of antidiscrimination law, employers cannot intentionally discriminate on the basis of sex.’ This guarantee of a workplace free of discrimination arises out of both the Equal Protection Clause2 and, even more directly, Title VII of the Civil Rights Act of 1964. A closer look, however, reveals that, in some circumstances, Title VII actually permits blatant, explicit sex discrimination. For example, under Title VII, a hospital can categorically exclude men from obstetrics-gynecological (“ob-gyn”) nursing positions. How can this be the case? Despite its general prohibition of employment discrimination on the basis of sex, Title VII carves out an exception for sex-specific hiring practices justified because of a so-called “bona fide occupational qualification,” or “BFOQ.” If an employer can demonstrate that simply being a woman or a man is an essential part of the job, the BFOQ provision immunizes that employer from liability under Title VII. In the years immediately following the passage of Title VII, employers tried to utilize the BFOQ exception to preserve discriminatory policies that made it more difficult for women and men to take non- traditional jobs. Employers would suggest that women were not strong. enough to perform physically intensive work, such as telephone repair. Men, on the other hand, were characterized as not soothing or sexy enough to hold certain service jobs, such as flight attendants. Courts have generally rejected these explanations as merely perpetuating the stereotypes that prevent men and women from breaking out of traditional sex-identified roles.